1987
DOI: 10.1128/mcb.7.2.799
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein synthesis in decay and accumulation of mRNA during spore germination in the cellular slime mold Dictyostelium discoideum.

Abstract: Spore germination in Dictyostelium discoideum is a particularly suitable model for studying the regulation of gene expression, since developmentally regulated changes in both protein and mRNA synthesis occur during the transition from dormant spore to amoeba. The previous isolation of three cDNA clones specific for mRNA developmentally regulated during spore germination allowed for the quantitation of the specific itlRNAs during this process. The three mRNAs specific to clones pLK109, pLK229, and pRK270 have h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A role for translational efficiency in the regulation of mRNA stability is suggested by the destabilizing effects of drugs which disrupt mRNAribosome association (1,33), premature translational termination codons (41,45), and clustered rare codons (26). For all three types of effects it has been postulated that, when ribosome association is diminished or eliminated, mRNA degradation is enhanced by the increased access of specific nucleases to the mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for translational efficiency in the regulation of mRNA stability is suggested by the destabilizing effects of drugs which disrupt mRNAribosome association (1,33), premature translational termination codons (41,45), and clustered rare codons (26). For all three types of effects it has been postulated that, when ribosome association is diminished or eliminated, mRNA degradation is enhanced by the increased access of specific nucleases to the mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these complex decay kinetics reflect the sum of the decay rates of individual mRNAs (e.g., in D. discoideum, the most stable mRNAs have half-lives of approximately 10 h and the least stable mRNAs have half-lives which are approximately 10-fold shorter). It has been suggested that such large differences in the stability of individual mRNAs could be accounted for by differences in their respective sizes (39,52,58,63,78,81), poly(A) tail lengths (8,28,56,91), ribosome loading (1,26,33,41,45), or 5'-and 3'-untranslated (UT) sequences (42,53,64,69,74,76,89). To test the validity of these hypotheses, we have identified cloned cDNAs which encode mRNAs that are representative of the stability extremes in D. discoideum and have initiated a characterization of the properties of the respective mRNAs.…”
mentioning
confidence: 99%
“…Development was initiated by removing bacteria or nutrient broth, followed by plating the cells as described previously (31). Cycloheximide, when used, was present at 400 ,ug/ml, and pactamycin (gift of The Upjohn Co., Kalamazoo, Mich.) was used at 300 jig/ml (17). Inhibition of protein synthesis was determined as outlined by Finney et al (11).…”
Section: Methodsmentioning
confidence: 99%
“…The stabilization of these short-lived mRNAs by either inhibitors of initiation or elongation indicates a requirement for continuing protein synthesis in the decay of these mRNAs. However, the mRNAs for tyrosine aminotransferase (42), vesicular stomatitis (33), and several proteins of Dictyostelium discoideum (22) were found to be stable in the presence of cycloheximide but not in the presence of pactamycin or puromycin. These later findings have suggested that shielding of mRNA by polysomes (which occurs when elongation but not initiation is inhibited) may protect against mRNA decay (3,22,37).…”
mentioning
confidence: 99%
“…However, the mRNAs for tyrosine aminotransferase (42), vesicular stomatitis (33), and several proteins of Dictyostelium discoideum (22) were found to be stable in the presence of cycloheximide but not in the presence of pactamycin or puromycin. These later findings have suggested that shielding of mRNA by polysomes (which occurs when elongation but not initiation is inhibited) may protect against mRNA decay (3,22,37). Although the use of translational inhibitors has failed to provide evidence for a general mechanism for mRNA degradation, it has accentuated the importance of interactions of mRNA with components of the translational apparatus in the destabilization of mRNA.…”
mentioning
confidence: 99%